Comic Design Using the Canva Application with Critical Thinking Enhancement on the Topic of Hindu and Buddhist Historical Heritage in Elementary School - Nanindya Filanti Tiaeni; Shofi Nur Amalia; Cindya Alfi (Global Action and Education for Society, 2026)
The delivery of material using physical books as the main source makes the learning process less attractive to students, especially in history learning. Generally, this is due to the abundance of material to be learned and teachers who are fixated on lecturing methods. Developing learning media design in comic format is one solution proposed by researchers in this study. This study aims to create an effective and practical learning media design to support the teaching-learning process and improve studdent’s critical thinking skills, especially in historical studies. The research and development method used in this study refers to the ASSURE model, which consists of six stages tailored to needs. The validation results by media experts showed a score of 89%, material experts scored 92%, and linguists scored 87%. The assessment of the product's appeal was conducted by 5th-grade teachers, who gave a perfect score of 100%. The target group for product testing was 26th students from five grade at 1ST Sukorejo Elementary School, Sutojayan District, who achieved an average final score of 85% in the critical thinking skills category. Based on the research results, it can be concluded that this learning media is feasible and attractive for use in teaching-learning activities